Marketing Intelligence in Islamic Education: A Model for Enhancing Competitiveness through the Use of Digital Data - Mohammad Abdul Aziz Al Wahedi; Muhammad Kholilur Rohman; Mohammad Holidi; Thoiful Abrar; Mohammad Rofik (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study examines the role of marketing intelligence in enhancing the competitiveness of Islamic educational institutions through the strategic utilization of digital data. Rapid digital transformation has intensified competition among educational institutions, creating a need for data-driven decision-making capabilities that extend beyond conventional marketing approaches. Using a quantitative explanatory design, data were collected from leaders, marketing managers, public relations officers, and digital communication personnel from Islamic schools, pesantren, and Islamic higher education institutions. The proposed model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings demonstrate that marketing intelligence constitutes a multidimensional capability encompassing digital data acquisition, market sensing capability, stakeholder intelligence, competitive intelligence, and analytical capability. Measurement model evaluation confirmed the reliability and validity of all constructs. Structural analysis revealed that analytical capability, stakeholder intelligence, and competitive intelligence exert significant positive effects on institutional competitiveness. The validated model indicates that competitive advantage is generated not merely through digital technology adoption but through the organizational capacity to transform digital information into strategic knowledge. The study contributes to educational management literature by providing an empirically validated framework linking digital data utilization, marketing intelligence, and institutional competitiveness in Islamic education.